Analisis Kemampuan Guru dalam Membuat dan Memanfaatkan Media Pembelajaran - Vina Dwi Setiyani; Sri Harmianto (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2022)
AbstractThe learning video medium is one of the audiovisual media that presents audio and visual to help the teaching-learning process and achieve learning objectives. This research aimed to describe the teachers' skills in making and utilizing learning video media inSD Muhammadiyah Cipete using a qualitative approach. The participants included the first to sixth-grade teachers, students, and the school principal. The data were collected using observation, interviews, and documentation. The results showed that all teachers were able to make and utilize learning video media to help deliver learning materials during online learning. This research concluded that teachers should have a good skill in using information technology to make and use video learning media. They could join a training about making, editing, and accessing the learning video to improve their skills.